Iron Objects from Bagaevka Settlement - Leonard F. Nedashkovsky; Marat B. Shigapov (Археология евразийских степей, 2022)
Some types of iron wares from Bagaevka settlement of the second half of 13th – 14th century, situated in periphery of the Golden Horde city Ukek in Saratov area of Saratov region are analyzed in the paper. Settlement was excavated by expedition of Kazan University under supervision of L.F. Nedashkovsky in 2002–2003, 2006–2012, 2014–2016 and 2020–2021. Bagaevka settlement is quite large rural settlement; the area of the site is 5.1 hectares, the thickness of the cultural layer in some places reaches more than 90 cm. Numismatic finds from the site belong to the Golden Horde mintage of the last quarter of 13th – beginning of 60s of 14th century. The authors consider iron pintles, plates, handles and undefined objects, for which assumptions about their functional purpose are given. This complex characterizes material culture of the Golden Horde village of the Lower Volga region.